Implementasi Strategi Pemasaran di PT. Bank Tabungan Negara (Persero) pada tahun 2020 - Hanan Wihasto (Program Studi Manajemen, 2020)
So far, Bank BTN has distributed more KPR Package A and B for low-income groups of people, so that people tend to be more familiar with KPR BTN only for Simple Houses (RS) and Very Simple Houses (RSS). In fact, in addition to that, Bank BTN also has a KPR product for middle, semi-luxurious and luxurious homes, which is called the Griya Utama Credit. Based on the aforementioned competition, we limit the formulation of the problem to the assessment of the implementation of the marketing strategy at PT. Bank Tabungan Negara (Persero) in 2020. The purpose of this study is to assess the implementation of the marketing strategy of PT. Bank Tabungan Negara (Persero) and evaluating the strengths, weaknesses, opportunities and threats of PT. Bank Tabungan Negara (Persero), so it can be seen the existence of Bank BTN in this industrial business. After calculating with a SWOT analysis, then the strengths and weaknesses are compared. If the strength value is greater than the weakness value, it can be said that the company's position is relatively stronger than its competitors or vice versa. Likewise with the comparison between opportunities and threats, if the opportunity value is greater than the threat, then it means that the company has a greater opportunity than the threat it faces. All data that will be required in this study were obtained from oral / written interviews with the Head of Division, Head of Division or Members of the Board of Directors of Bank BTN.